Association between inflammation- and nutrition-related indicators and mortality in patients with heart failure: a cohort study - Liu, Songtao; Fu, Ting; Deng, Tianhua; Cai, Xinyong; Zhan, Yuliang; Zhu, Hongmin (Frontiers in Nutrition, 2025)
ObjectiveInflammation and malnutrition are critical in heart failure (HF) progression. This study evaluated the prognostic value of inflammation- and nutrition-related indicators for mortality in HF.MethodsRetrospective analysis of 1999–2018 NHANES data (101,316 participants, 1,500 HF patients) assessed indicators including advanced lung cancer inflammation index (ALI), monocyte-to-albumin ratio (MAR), neutrophil-to-albumin ratio (NAR), red cell distribution width-to-albumin ratio (RAR), prognostic nutritional index (PNI), geriatric nutritional risk index (GNRI), hemoglobin-albumin-lymphocyte-platelet (HALP) score and controlling nutritional status (CONUT) score. Associations with all-cause and cardiovascular mortality were analyzed via Kaplan–Meier curves, Cox regression, restricted cubic spline, time-dependent ROC, and random survival forest (RSF).ResultsA total of 1,500 HF patients were included in the final analysis. Kaplan–Meier analysis demonstrated that elevated MAR, NAR, RAR, and CONUT scores were linked to higher mortality, whereas elevated ALI, PNI, GNRI, and HALP scores were associated with lower mortality in HF patients. After false discovery rate (FDR) correction, the majority of indicators (including ALI, RAR) remained significantly associated with mortality in multivariable Cox models. Time-dependent ROC analysis demonstrated that RAR exhibited the strongest predictive ability for 1-year all-cause mortality (AUC = 0.768, 95% CI: 0.718–0.819) and cardiovascular mortality (AUC = 0.788, 95% CI: 0.725–0.851). In contrast, ALI showed the best predictive performance for mortality at 3 years (all-cause: AUC = 0.690, 95% CI: 0.654–0.726; cardiovascular: AUC = 0.705, 95% CI: 0.655–0.756), 5 years (all-cause: AUC = 0.679, 95% CI: 0.647–0.711; cardiovascular: AUC = 0.677, 95% CI: 0.633–0.721), and 10 years (all-cause: AUC = 0.691, 95% CI: 0.657–0.725; cardiovascular: AUC = 0.699, 95% CI: 0.656–0.742). These findings were consistent with the C-index results. RSF analysis, validated by an internal hold-out test, consistently identified ALI as a leading predictor of mortality risk.ConclusionCompared with other inflammation- and nutrition-related indicators, RAR and ALI may provide superior predictive value for short-term and long-term mortality risk, respectively, in HF patients.